Implementación del proceso de selección de personal en la Unidad Educativa San Patricio (UESPA) de la Fundación Proyecto Salesiano Chicos de la Calle Zona Norte. - Román San Andrés, María José (2016)
San Patricio Education Unit UESPA contributes through its education programs to eradicate the existence of children in the street. Their work contributes to the strengthening of society these being essential to ensure respect for and inclusion of children and adolescents in Ecuador. Therefore, the objective of this research focuses on the evaluation of the different recruitment processes currently applied, identifying weaknesses that can be improved to benefit the quality of services rendered. As such, its development poses alternatives for effective staffing, which have been defined using the Balanced Scorecard as the main tool. Its use led the need to identify and update the organizational structure of the academic area, defining the required profiles as well as the call and selection processes for recruitment aligned to the needs. Its development included process mapping to provide proper guidance that adds value to the institution and allows processes to provide high quality education. Finally, management indicators with which to evaluate compliance with the implementation of the proposal were raised. Once defined, it is concluded that it is feasible to be used, with a pioneering process that starts with a philosophy of continuous improvement in the institution where staff contribute to improving the quality of life of children and adolescents.